2020
DOI: 10.3389/fonc.2020.01391
|View full text |Cite
|
Sign up to set email alerts
|

Conventional Two-Stage Hepatectomy or Associating Liver Partitioning and Portal Vein Ligation for Staged Hepatectomy for Colorectal Liver Metastases? A Systematic Review and Meta-Analysis

Abstract: Background: Pushing the surgical limits for initially unresectable colorectal liver metastases (CRLM) are two approaches for sequential liver resection: two-stage hepatectomy (TSH) and associating liver partitioning and portal vein ligation for staged hepatectomy (ALPPS). However, the role of each treatment modality remains ill-defined. The present meta-analysis was designed to compare the safety, efficacy, and oncological benefits between ALPPS and TSH in the management of advanced CRLM. Methods: A systematic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 70 publications
1
11
0
1
Order By: Relevance
“…We also demonstrated the feasibility and safety of ALPPS in a low-volume centre. Our overall morbidity was 60%, which is comparable to overall minor complications of 59% reported in a meta-analysis on 161 patients who underwent ALPPS [3]. Our results were also similar to results reported by other low-volume centres (overall post-operative complication rate 66.7%) [23].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…We also demonstrated the feasibility and safety of ALPPS in a low-volume centre. Our overall morbidity was 60%, which is comparable to overall minor complications of 59% reported in a meta-analysis on 161 patients who underwent ALPPS [3]. Our results were also similar to results reported by other low-volume centres (overall post-operative complication rate 66.7%) [23].…”
Section: Discussionsupporting
confidence: 89%
“…To reduce this risk, guidelines state a minimum of future liver remnant (FLR) > 20-25% in healthy patients without underlying liver disease prior to extended hepatectomy [ 2 ]. Associating Liver Partition and Portal vein ligation for Staged hepatectomy (ALPPS) is a two-staged procedure aimed to induce rapid hypertrophy of the FLR to reduce risk of PHLF, with higher successful completion of second stage of hepatectomy (98% vs. 78%, odds ratio [OR] = 5.75, p < 0.001), R0 resection (66% vs. 37%, OR = 4.68, p < 0.001) and shorter waiting time between the first and second stage of hepatectomy (11.6 vs. 45.7 days, weighted mean difference [MD] = −35.3 days, p < 0.001) compared to conventional two-stage hepatectomy (TSH) [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the same paper, oncological outcomes after ALPPS procedure seem to be likewise comparable to LVD results, with a 3-year OS of 37% and a median DFS of 19 months [ 35 ]. Similarly, a very recent meta-analysis comparing ALPPS with a traditional two-stage hepatectomy found a 1-year OS of 79 vs. 84% respectively for ALPPS and PVE [ 36 ]. A recent meta-analysis by Giglio et al has also reported that PVE does not negatively affect oncological outcomes after major liver resections in patients with CRLM [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Considering this within the context of the literature, several papers show similar results. For example, Vicente et al found an SFSS rate of 22.2% [ 35 ], and Zhang et al indicated that 75% of ALPPS-associated mortality was due to post hepatectomy liver failure [ 36 ]. In addition, a recent review by Chan et al from 2020 highlights that the main complications of ALPPS are high morbidity (Clavien-Dindo ≥ Grade IIIB complications) and 90-day mortality.…”
Section: Discussionmentioning
confidence: 99%